(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: One of the main causes of pain and impairment worldwide is knee osteoarthritis (KOA). Knee osteoarthritis (OA), commonly known as degenerative joint disease, is frequently brought on by wear-and-tear and articular cartilage loss that occurs over time which causes functional restrictions, disability, and ultimately a decline in a person’s quality of life. Objective: To assess the quality of life in Knee Osteoarthritis patients. Methodology: This Cross-Sectional study was conducted among knee osteoarthritis patient population from government hospitals in Rawalpindi and Islamabad from March to August 2023. A 133 sample size by using Slovin’s formula sample was calculated, 115 participants met inclusion criteria and 18 were excluded according to exclusion criteria. A semi structural questionnaire was distributed among participants; it included questions related to demographics, questions of inclusion exclusion criteria, and SF-36 Scale. Data was analyzed by SPSS version 25; results were obtained in form of frequency and percentage. Results: Total 133 participants were taken for the study with mean age of 50.2 years (range from 40 to 60). The scores of domains are general health (30), physical functioning (35), energy (40), pain (45), mental health (52), social functioning (50), Role limitation due to physical health (75), and Role limitation due to emotional problems (100). Conclusion: Findings of our data suggest that patients with knee osteoarthritis have a low perception of their quality of life especially general health, physical functioning and energy domains. Quality of life is impaired more in females than male.